Intraoperative Hemifacial Composite Flap Perfusion Assessment Using Spatial Frequency Domain Imaging: A Pilot Study in Preparation for Facial Transplantation. Issue 2 (February 2016) - Vargas, Christina R.; Nguyen, John T.; Ashitate, Yoshitomo; Angelo, Joseph; Venugopal, Vivek; Kettenring, Frank; Neacsu, Florin; Frangioni, John V.; Gioux, Sylvain; Lee, Bernard T.
Abstract : Background: Vascularized composite allotransplantation represents an important advancement in the field of reconstructive microsurgery and has continued to increase in popularity. The significant clinical morbidity associated with flap failure represents an important barrier to even more widespread use of these techniques. Early identification of vascular compromise has been associated with a higher salvage rate, yet most surgeons rely only on clinical assessment intraoperatively. Spatial frequency domain imaging (SFDI) presents a noncontact, objective measurement of tissue oxygenation over a large field of view. This study aims to evaluate the use of SFDI technology in hemifacial composite flap compromise as could occur during facial transplant. Methods: Six composite hemifacial flaps were created in three 35-kg Yorkshire pigs and continuously imaged using SFDI before, during, and after 15-minute selective vascular pedicle occlusion. Arterial and venous clamping trials were performed for each flap. Changes in oxyhemoglobin concentration, deoxyhemoglobin concentration, and total hemoglobin were quantified over time. Results: The SFDI successfully measured changes in oxygenation parameters in all 6 composite tissue flaps. Significant changes in oxyhemoglobin, deoxyhemoglobin, and total hemoglobin were seen relative to controls. Early and distinct patterns of alteration were noted in arterial and in venous compromise relative to one another. Conclusions: The need for noninvasive, reliable assessment of composite tissue graft viability is apparent, given the morbidity associated with flap failure. The results of this study suggest that SFDI technology shows promise in providing intraoperative guidance with regard to pedicle vessel integrity during reconstructive microsurgery.